Laboratory study of the combined wave and surge overtopping-induced normal stress on dike - Zhou, Zijun; Sun, Zhongbing; Zhou, Yiren; Zuo, Qihua; Wang, Hongchuan; Chen, Yongping; Huang, Feiyang (Frontiers in Marine Science, 2023)
Normal stress on dike is one of the most critical parameters for sound dike design. With more rapidly rising sea levels due to global warming, dikes are deeply threatened by overtopping induced from combined wave and storm surge. Compared with wave overtopping on positive freeboard, the curling breaking-wave on dike induced by combined wave and surge overtopping may destroy the weakly protected dike crest and landward slope. Thus, in order to prevent severe damages of dikes, it is necessary to fully understand the normal stress induced by combined wave and surge overtopping. In this paper, physical model tests are carried out to study the normal stress on dike induced by combined wave and surge overtopping. Two characteristics of the normal stress on dike are observed. The spatial distribution of normal stress on dike is analyzed. It is found that the Weibull distribution can be used to well describe the statistical distribution of peak normal stresses. Furthermore, by curve fitting of the laboratory measured data, the Weibull factors on the part of crest and the upper part of landward slope are obtained respectively.